The Role of Creativity, Challenges, and MSME Management Strategies in Empowering Generation Z - Situmorang, Anggi Ardani Br; Rizky, M. Chaerul; Adinata, Aqilla Tri; Wulandari, Dwi; Oktavia, Suci (LifeSciFi, 2025)
This study investigates the influence of creativity and challenges on the management strategies of Micro, Small, and Medium Enterprises (MSMEs) operated by Generation Z in Medan City. As digital natives, Generation Z is recognized for their innovative mindset, technological adaptability, and potential as future entrepreneurs. Using a quantitative approach with multiple linear regression analysis, data were collected through questionnaires distributed to 36 Gen Z MSME actors. Validity and reliability tests confirmed that all research instruments were both valid and reliable. The findings reveal that creativity and challenges simultaneously have a significant impact on MSME management strategies. Partially, creativity shows a significant influence, highlighting the importance of innovative thinking in product development, marketing, and branding. However, challenges emerge as the more dominant factor, reflecting Gen Z’s resilience and adaptability in navigating market competition, limited capital, and evolving consumer expectations. These results suggest that successful MSME management by Gen Z relies not only on creativity but also on the ability to transform challenges into strategic opportunities. The study concludes by recommending the enhancement of Gen Z’s entrepreneurial competencies through targeted training programs that foster creativity and equip them with tools to respond to dynamic business environments.